ANALISIS IDIOM BAHASA KOREA MENGGUNAKAN LEKSEM MATA - Budiarto, Maharani Tsani; Nurfitriana Ansas, Velayeti; Widyana, Ashanti (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
This study aims to describe the idiomatic meaning of the lexeme